Paintings as alternative investment: Evidence from Turkey - Balcı, Rıza (İstanbul Bilgi Üniversitesi, 2016)
[Abstract Not Available]
Alternatif yatırım aracı olarak resim sanatı: Türkiye üzerinde bir çalışma